A Prayer for Relief: Assessing the Constitutionality of Missouri’s Right to Pray Amendment - Meredith Schlacter (Washington University Journal of Law & Policy, 2014)
On August 7, 2012, the state of Missouri passed by popular vote the Religious Freedom in Public Places amendment. The summary that appeared on the ballot in August asserted the amendment would ensure Missourians’ right to express their religious beliefs and mandate all public schools display the Bill of Rights of the United States Constitution. The full text of the amendment, however, is quite distinct from the more innocuous language that appeared on the ballot. The discrepancy between the ballot language and the substance of the amendment immediately sparked litigation. This Note reviews the history of the Religious Freedom in Public Places amendment, including the legislative history of the amendment and the controversy that has met its passage. It also examines relevant constitutional provisions and prior court decisions addressing religion and the government. Then, this Note analyzes Missouri’s Religious Freedom in Public Places amendment and considers whom it protects and whom it is likely to hurt. Then, this Note argues the amendment is unconstitutional and considers the legal responses available for challenging it, including legislative and litigation-based strategies. This Note proposes that the amendment should be invalidated in federal court under either the Establishment Clause or the Free Exercise Clause of the First Amendment to the United States Constitution.
Keywords: Religious Freedom in Public Places Amendment; Right to Pray Amendment; Coburn v. Mayer; prayer in school; religious expression; First Amendment; Free Exercise Clause; Establishment Clause; Missouri Right to Pray Amendment